CONTENTS, PROBLEMS AND DIDACTICAL BASIS OF TEACHING THE SUBJECT "ELECTRIC LIGHTING" IN THE ELECTRONIC EDUCATIONAL ENVIRONMENT - F. N. Nasretdinova (Journals Park Publishing, 2023)
The maximum effectiveness of the process of preparation for the e-learning environment can be achieved only through the coordinated development of psychological, technical, technological, information, legal, methodological and other components of the process. The introduction of modern information and communication technologies into the educational process has led to the creation of a new form of teaching - distance learning - in addition to traditional teaching methods.
Keywords: Learning environment, educator, learner, educational programs, educational subjects.